Perception of the Extension Agents Regarding Information Sources of Sustainable Agriculture in Sindh Province of Pakistan - Muhammad Ismail Kumbhar; Saghir Ahmed Sheikh; Shuhabuddin Mughal; Mahvish Jabeen Channa (Journal of Basic & Applied Sciences, 2021)
The study was undertaken in Sindh province to examine the extension agents perceptions of various sources of information. This study used a descriptive research design and the target population was Extension Agents. A representative sample of 162 Extension agents was proposed from six districts of Sindh, namely, 1. Larkana 2. Naushehro Feroze 3. Shaheed Benazirabad 4. Sanghar 5. Mirpurkhas 6. Badin representing the agro-ecological zones of Sindh province. The majority of the respondents 49.38% having their age in the range of 31-45 years. The data revealed that majority of the extension personnel 43.21% of the respondents were graduate level of education. The diploma holder’s respondents were 24.69%. The majority of the extension personnel (43.21%) had job experience 21-30 years. Only 6.17% of the extension personnel had job experience of more than 31 years. The most frequent sources of information was perceived by extension agents about sustainable agriculture were television broadcasts,. However, Internet / Computers, Books and Manuals, Middle Man, and Electronic Devices (Mobile, Fax and other sources). The majority of the respondents perceived that Lack of effective monitoring (reporting and supervision) (M=1.26, SD=.058), Lack of Linkage between Research and Extension (M=1.06, SD=.025), Shortage of time to teach farmer properly (M=1.21, SD=.042), Illiteracy among farmers (M=1.141, SD=.061) and Lack of transportation facilities (M=1.21, SD=.042)as higher barrier that hampering the promotion and adoption of sustainable agriculture practices in the areas where they worked, this implies that proper guidelines and teaching aids had not been given to the extension worker to effectively work and communicate with the local farmer. However in sufficient funding for agriculture extension (M=1.71, SD=.061 Lack of means for upgrading qualification M=1.93, SD=.048), Large farm area (M=1.85, SD=.065), Lack of In-service Courses M=2.00, SD=.040), More time and management M=2.00, SD=.000) and Lack of Information about Sustainable Agriculture Technologies M=2.00, SD=.000) were perceived as a low barrier in adoption of sustainable agriculture practices.. This study will enable policy makers to effectively transfer the technology for sustained growth and will enhance farmers understanding about the concept of sustainable agriculture.